Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/ijlh.12775
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of reduced thrombin generation and/or decreased platelet response in women with unexplained heavy menstrual bleeding

Abstract: Our approach in women with HMB using a high precision platelet function test in combination with thrombin generation showed impaired coagulation or impaired platelet function in more than 40% of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…The existing literature and expert committees recommend to screen on coagulation disorders in women suffering from HMB in gynaecological practice before surgical treatment 17,28 . Our findings emphasize that gynaecologists should be aware of impaired coagulation, which might influence the outcome of endometrium ablation 29,30 …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The existing literature and expert committees recommend to screen on coagulation disorders in women suffering from HMB in gynaecological practice before surgical treatment 17,28 . Our findings emphasize that gynaecologists should be aware of impaired coagulation, which might influence the outcome of endometrium ablation 29,30 …”
Section: Discussionmentioning
confidence: 72%
“…29,30 Doherty et al described that menorrhagia scores in BATs increase remarkably with aging in healthy women related to the procedurespecific accumulation in HMB management from medical treatment till surgical interventions. When assessed by age quartiles, the nor-…”
mentioning
confidence: 99%
“…However, besides implementation of NGS techniques, functional haemostatic assays need to be improved. Currently, flow cytometry‐based platelet function diagnostic tests are being developed and global haemostatic assays are implemented in clinical practice …”
Section: Discussionmentioning
confidence: 99%
“…Currently, flow cytometry-based platelet function diagnostic tests are being developed and global haemostatic assays are implemented in clinical practice. [38][39][40]…”
Section: However Besides Implementation Of Ngs Techniques Functionalmentioning
confidence: 99%
“…Statistically significant difference is denoted by *** = P ≤ 0.001. more specialised laboratories. Furthermore, a recent study by Eising et al reported a high prevalence of reduced thrombin generation and/or decreased platelet response in women with unexplained heavy menstrual bleeding, implicating the need for more specialised laboratory tests [23].…”
Section: Discussionmentioning
confidence: 99%